2016
DOI: 10.1021/jacs.6b07612
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Electrolyte Cations Enhances the Electrochemical Reduction of CO2 over Ag and Cu

Abstract: Electrolyte cation size is known to influence the electrochemical reduction of CO over metals; however, a satisfactory explanation for this phenomenon has not been developed. We report here that these effects can be attributed to a previously unrecognized consequence of cation hydrolysis occurring in the vicinity of the cathode. With increasing cation size, the pK for cation hydrolysis decreases and is sufficiently low for hydrated K, Rb, and Cs to serve as buffering agents. Buffering lowers the pH near the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

66
954
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 785 publications
(1,024 citation statements)
references
References 32 publications
66
954
2
2
Order By: Relevance
“…It was not until very recently that their roles in CO 2 RR received careful investigations. Based on their experimental observation, Bell and co‐workers proposed that the p K a for cation hydrolysis decreased from Li + to Cs + in their bicarbonate electrolyte, and larger cations such as K + , Rb + , and Cs + had p K a values sufficiently low that they could act as buffering agents and lower the local pH near the cathode, leading to increased ethylene selectivity and lowered Faradaic efficiency for H 2 on electropolished Cu foils 60. The CO 2 RR performance of Cu can also be tuned with the addition of halide anions to the electrolyte.…”
Section: Electrocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
“…It was not until very recently that their roles in CO 2 RR received careful investigations. Based on their experimental observation, Bell and co‐workers proposed that the p K a for cation hydrolysis decreased from Li + to Cs + in their bicarbonate electrolyte, and larger cations such as K + , Rb + , and Cs + had p K a values sufficiently low that they could act as buffering agents and lower the local pH near the cathode, leading to increased ethylene selectivity and lowered Faradaic efficiency for H 2 on electropolished Cu foils 60. The CO 2 RR performance of Cu can also be tuned with the addition of halide anions to the electrolyte.…”
Section: Electrocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
“…A number of studies have shown that one way of influencing the product distribution is through changes in the electrolyte cation. [8][9][10][11][12][13] The role of cations is particularly interesting because a number of studies have shown that both the activity and selectivity of Ag, Hg, and Cu for the CO 2 reduction reaction (CO 2 RR) are influenced significantly by the size of the alkali metal cation in the electrolyte. [8][9][10][11][12][13] Similar effects have also been observed for the electrochemical reduction of oxygen, the oxidation of hydrogen, and the oxidation of low molecular weight alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] The role of cations is particularly interesting because a number of studies have shown that both the activity and selectivity of Ag, Hg, and Cu for the CO 2 reduction reaction (CO 2 RR) are influenced significantly by the size of the alkali metal cation in the electrolyte. [8][9][10][11][12][13] Similar effects have also been observed for the electrochemical reduction of oxygen, the oxidation of hydrogen, and the oxidation of low molecular weight alcohols. [14][15][16][17][18] For Ag and Hg, which are selective for CO 2 reduction to carbon monoxide (CO) and formate anions (HCOO -), respectively, increasing the alkali metal cation size increases the rates of formation of these products.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations